¿Levantar la mano sobre uno mismo? : jean améry y su crítica a la condenación moral del suicidio (2020)
The aim of the present work has been to understand objective and question the negative conception of suicide, its historical development as well as those unconventional postures that allow resignification in relation to concepts such as belonging, justice, duty, freedom, responsibility, among others, from which raises under what conditions or circumstances it is possible to affirm that human beings can decide freely and voluntarily the end of their existence.